How do you solve $\ln x + \ln (x - 2) = 1$?
Answer
Verified
441.9k+ views
Hint: In this question we will use the properties of logarithm and apply it to both sides of the equation to simplify the equation and solve it for the value of $x$.
Formula used:
$({x_1},{x_2}) = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2ac}}$, Where $(x,y)$ are the roots of the equation and $a,b,c$ are the coefficients of the terms in the quadratic equation.
Complete step-by-step answer:
We have the question given us to as:
$ \Rightarrow \ln x + \ln (x - 2) = 1$
Now we know the property of logarithm that $\ln a + \ln b = \ln ab$ therefore, on using this property, we get:
$ \Rightarrow \ln [x(x - 2)] = 1$
Now on taking the antilog on both the sides, we get:
$ \Rightarrow x(x - 2) = {e^1}$
Now on multiplying the terms in the left-hand side, we get:
$ \Rightarrow x \times x - x \times 2 = e$
On simplifying we get:
$ \Rightarrow {x^2} - 2x = e$
On transferring the term $e$ from the right-hand side to the left-hand side, we get:
$ \Rightarrow {x^2} - 2x - e = 0$
Now the given equation is in the form of a quadratic equation therefore, to find the value of $x$, we will factor the equation.
Since the middle term cannot be directly split to factorize the equation, we will use the quadratic formula to get the solution.
Now we have $a = 1$, $b = - 2$and $c = - e$
The roots can be found out as:
$ \Rightarrow ({x_1},{x_2}) = \dfrac{{ - ( - 2) \pm \sqrt {{{( - 2)}^2} - 4(1)( - e)} }}{{2(1)( - e)}}$
On simplifying, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm \sqrt {4 + 4e} }}{2}\]
On taking out $4$as common in the root, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm \sqrt {4(1 + e)} }}{2}\]
On taking the square root of $4$, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm 2\sqrt {1 + e} }}{2}\]
Now on taking out $2$as common from the numerator we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2(1 \pm \sqrt {1 + e} )}}{2}\]
On simplifying, we get:
\[ \Rightarrow ({x_1},{x_2}) = 1 \pm \sqrt {1 + e} \]
Therefore, the roots are: \[{x_1} = 1 + \sqrt {1 + e} \] and \[{x_2} = 1 - \sqrt {1 + e} \]
Now since the logarithm of a negative number does not exist, we discard ${x_2}$ therefore, the root is:
\[{x_1} = 1 + \sqrt {1 + e} \], which is the required solution.
Note:
It is to be noted that the logarithm we are using has the base $10$, the base is the number to which the log value has to be raised to, to get the original term. This is also called the antilog of the number which is the logical reverse of taking a log.
The most commonly used bases in logarithm are $10$ and $e$ which has a value of approximate $2.713...$
Logarithm is used to simplify a mathematical expression; it converts multiplication to addition, division to subtraction and exponents to multiplication.
Formula used:
$({x_1},{x_2}) = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2ac}}$, Where $(x,y)$ are the roots of the equation and $a,b,c$ are the coefficients of the terms in the quadratic equation.
Complete step-by-step answer:
We have the question given us to as:
$ \Rightarrow \ln x + \ln (x - 2) = 1$
Now we know the property of logarithm that $\ln a + \ln b = \ln ab$ therefore, on using this property, we get:
$ \Rightarrow \ln [x(x - 2)] = 1$
Now on taking the antilog on both the sides, we get:
$ \Rightarrow x(x - 2) = {e^1}$
Now on multiplying the terms in the left-hand side, we get:
$ \Rightarrow x \times x - x \times 2 = e$
On simplifying we get:
$ \Rightarrow {x^2} - 2x = e$
On transferring the term $e$ from the right-hand side to the left-hand side, we get:
$ \Rightarrow {x^2} - 2x - e = 0$
Now the given equation is in the form of a quadratic equation therefore, to find the value of $x$, we will factor the equation.
Since the middle term cannot be directly split to factorize the equation, we will use the quadratic formula to get the solution.
Now we have $a = 1$, $b = - 2$and $c = - e$
The roots can be found out as:
$ \Rightarrow ({x_1},{x_2}) = \dfrac{{ - ( - 2) \pm \sqrt {{{( - 2)}^2} - 4(1)( - e)} }}{{2(1)( - e)}}$
On simplifying, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm \sqrt {4 + 4e} }}{2}\]
On taking out $4$as common in the root, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm \sqrt {4(1 + e)} }}{2}\]
On taking the square root of $4$, we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2 \pm 2\sqrt {1 + e} }}{2}\]
Now on taking out $2$as common from the numerator we get:
\[ \Rightarrow ({x_1},{x_2}) = \dfrac{{2(1 \pm \sqrt {1 + e} )}}{2}\]
On simplifying, we get:
\[ \Rightarrow ({x_1},{x_2}) = 1 \pm \sqrt {1 + e} \]
Therefore, the roots are: \[{x_1} = 1 + \sqrt {1 + e} \] and \[{x_2} = 1 - \sqrt {1 + e} \]
Now since the logarithm of a negative number does not exist, we discard ${x_2}$ therefore, the root is:
\[{x_1} = 1 + \sqrt {1 + e} \], which is the required solution.
Note:
It is to be noted that the logarithm we are using has the base $10$, the base is the number to which the log value has to be raised to, to get the original term. This is also called the antilog of the number which is the logical reverse of taking a log.
The most commonly used bases in logarithm are $10$ and $e$ which has a value of approximate $2.713...$
Logarithm is used to simplify a mathematical expression; it converts multiplication to addition, division to subtraction and exponents to multiplication.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE
What will happen when any type of copper vessel is class 11 chemistry CBSE
The number of structural isomers possible for C4H8 class 11 chemistry CBSE
The number of vertebrae in rabbit is a 40 b 33 c 44 class 11 biology CBSE
Why is the wurtz reaction not preferred for the preparation class 11 chemistry CBSE